Fitness prospects: effects of age, sex and recruitment age on reproductive value in a long‐lived seabird. (22nd July 2014) - Zhang, He; Rebke, Maren; Becker, Peter H.; Bouwhuis, Sandra; Both, Christiaan
Summary Reproductive value is an integrated measure of survival and reproduction fundamental to understanding life‐history evolution and population dynamics, but little is known about intraspecific variation in reproductive value and factors explaining such variation, if any. By applying generalized additive mixed models to longitudinal individual‐based data of the common tern Sterna hirundo, we estimated age‐specific annual survival probability, breeding probability and reproductive performance, based on which we calculated age‐specific reproductive values. We investigated effects of sex and recruitment age (RA) on each trait. We found age effects on all traits, with survival and breeding probability declining with age, while reproductive performance first improved with age before levelling off. We only found a very small, marginally significant, sex effect on survival probability, but evidence for decreasing age‐specific breeding probability and reproductive performance with RA. As a result, males had slightly lower age‐specific reproductive values than females, while birds of both sexes that recruited at the earliest ages of 2 and 3 years (i.e. 54% of the tern population) had somewhat higher fitness prospects than birds recruiting at later ages. While the RA effects on breeding probability and reproductive performance were statistically significant, these effects were not large enough to translate to significant effects on reproductive value. Age‐specific reproductive values provided evidence for senescence, which came with fitness costs in a range of 17–21% for the sex‐RA groups. Our study suggests that intraspecific variation in reproductive value may exist, but that, in the common tern, the differences are small.